NNLO QCD corrections to associated W H production and H → b ¯ b decay - Caola, F; Luisoni, G; Melnikov, K; Roentsch, R (American Physical Society, 2018)
We present a computation of the next-to-next-to-leading-order (NNLO) QCD corrections to the production of a Higgs boson in association with a W boson at the LHC and the subsequent decay of the Higgs boson into a bb¯ pair, treating the b quarks as massless. We consider various kinematic distributions and find significant corrections to observables that resolve the Higgs decay products. We also find that a cut on the transverse momentum of the W boson, important for experimental analyses, may have a significant impact on kinematic distributions and radiative corrections. We show that some of these effects can be adequately described by simulating QCD radiation in Higgs boson decays to b quarks using parton showers. We also describe contributions to Higgs decay to a bb¯ pair that first appear at NNLO and that were not considered in previous fully differential computations. The calculation of NNLO QCD corrections to production and decay sub-processes is carried out within the nested soft-collinear subtraction scheme presented by some of us earlier this year. We demonstrate that this subtraction scheme performs very well, allowing a computation of the coefficient of the second-order QCD corrections at the level of a few per mill.